Diccionario de términos críticos de la literatura y la cultura en América Latina - Colombi, Beatriz (CLACSO, 2021)
The proposal to compile this dictionary of collective authorship arose from the interest and the need to reflect on the specialized lexicon in the area of studies of Latin American culture and literature. The selected terms refer to problems, contexts and diverse geocultural areas and, in this sense, make up a broad map of Latin American criticism. Seeking to make an assessment and update of the conceptual legacy that is representative of the cultural history of the continent, all the terms considered, articulated as an organic set through cross-references, give shape to Latin Americanism, a discursive formation crossed by controversies and subjected to a critical review in recent times. Reference and useful material for those interested in Latin American studies, both for young researchers and for specialists and readers in general.